2023
DOI: 10.3390/ijms241814347
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Immunotherapy Approaches for Treating Prostate Cancer

Lingbin Meng,
Yuanquan Yang,
Amir Mortazavi
et al.

Abstract: Immunotherapy has emerged as an important approach for cancer treatment, but its clinical efficacy has been limited in prostate cancer compared to other malignancies. This review summarizes key immunotherapy strategies under evaluation for prostate cancer, including immune checkpoint inhibitors, bispecific T cell-engaging antibodies, chimeric antigen receptor (CAR) T cells, therapeutic vaccines, and cytokines. For each modality, the rationale stemming from preclinical studies is discussed along with outcomes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 183 publications
0
4
0
Order By: Relevance
“…All of these data suggested antitumor activity. In comparison to the 3 mg/kg dose used in melanoma, more treatment-related grade 3 to 4 adverse events (TRAEs) were reported (40% vs. 23%), and there were 9 treatment-related deaths [246,251] (Table 1 Completed Immune checkpoint inhibitors Phase 3 clinical trials in prostate cancer [251][252][253][254][255][256][257][258] ). Median OS with Pembrolizumab + Docetaxel was 19.6 months (95%CI: 18.2 to 20.9) compared to 19.0 months (95%CI: 17.9 to 20.9) with Docetaxel alone.…”
Section: Overview Of Clinical Trials Involving Immune Checkpoint Inhi...mentioning
confidence: 99%
See 1 more Smart Citation
“…All of these data suggested antitumor activity. In comparison to the 3 mg/kg dose used in melanoma, more treatment-related grade 3 to 4 adverse events (TRAEs) were reported (40% vs. 23%), and there were 9 treatment-related deaths [246,251] (Table 1 Completed Immune checkpoint inhibitors Phase 3 clinical trials in prostate cancer [251][252][253][254][255][256][257][258] ). Median OS with Pembrolizumab + Docetaxel was 19.6 months (95%CI: 18.2 to 20.9) compared to 19.0 months (95%CI: 17.9 to 20.9) with Docetaxel alone.…”
Section: Overview Of Clinical Trials Involving Immune Checkpoint Inhi...mentioning
confidence: 99%
“…Primary endpoints were not met [257,258] . In the KEYNOTE-028 phase Ib study, pembrolizumab showed a 17.4% objective response rate (ORR) in 23 heavily treated mCRPC patients with measurable disease and ≥ 1% PD-L1 expression.…”
Section: Checkmate-7dx /Nct04100018mentioning
confidence: 99%
“…Prostate cancers are often resistant to immunotherapies. There are running research trials to approach immunotherapy for PCa, CRPC, and t-NEPC[ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the emerging immunotherapy approaches is given by Meng and co-workers [8]. In contrast to highly immunogenic malignancies, the immunosuppressive properties characterizing the microenvironment of PCa promote immune evasion, and this peculiarity has delayed the use of immunotherapy in the treatment of this disease [14].…”
mentioning
confidence: 99%